Assessment in geography education: a systematic review. Issue 1 (2nd January 2019) - Lane, Rod; Bourke, Terri
ABSTRACT: There are more than 700 articles exploring assessment in geography education. However, these papers vary in the degree to which recommendations and conclusions are based on research evidence. Globally, evidence-based practice is being prioritised, making it essential to understand exactly what the empirical research around this topic is saying. A systematic review provides a rigorous method for achieving such a task. This paper quantifies and systematically accounts for the proportion and scope of articles dedicated to assessment in geography education. We conclude that clarity is required regarding: (1) the essential geographical knowledge and skills students should develop; (2) the nature of the learning progressions in each of these areas; and (3) the types and formats of assessment instruments that will provide valid and reliable measures of this progress.